2016
DOI: 10.2105/ajph.2016.303163
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Screening of the “Birth Cohort” (Born 1945–1965) and Younger Inmates of New York City Jails

Abstract: Universal screening may be warranted pending further study including cost-effectiveness analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…In our study, nearly 100% of birth cohort patients engaged in care were screened with antibody testing for HCV, a screening rate significantly higher than the 21-64% reported in other populations also engaged in care. [24][25][26] Differences in practice setting and their established screening protocols (e.g., jail, primary care clinics, integrated care systems), as well as the higher rates of HCV risk factors observed in the underserved that may translate into heightened awareness of HCV among patients and providers, [27][28][29] may have contributed to the wide range of reported screening rates. Interestingly, with the introduction of the birth cohort recommendations, we observed the greatest rise in HCV screening and treatment among APIs, which may be attributed to lower rates of traditional HCV risk factors observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, nearly 100% of birth cohort patients engaged in care were screened with antibody testing for HCV, a screening rate significantly higher than the 21-64% reported in other populations also engaged in care. [24][25][26] Differences in practice setting and their established screening protocols (e.g., jail, primary care clinics, integrated care systems), as well as the higher rates of HCV risk factors observed in the underserved that may translate into heightened awareness of HCV among patients and providers, [27][28][29] may have contributed to the wide range of reported screening rates. Interestingly, with the introduction of the birth cohort recommendations, we observed the greatest rise in HCV screening and treatment among APIs, which may be attributed to lower rates of traditional HCV risk factors observed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…More than two-thirds of those who reported IDU were HCV antibody positive, a rate that is similar to rates reported in noncorrectional settings. 19 Because low HCV-related case fatality rates and long-lasting serostatus result in a direct correlation between duration of IDU and HCV prevalence, 20 the observed age-related increase in HCV antibody positivity 17 may be a function of cumulative risk resulting from increased exposure to IDU over time. Nearly 60% of people with HCV infection in our study reported IDU: because fear of self-incrimination and lack of confidentiality may prevent inmates from reporting IDU, this percentage may underestimate the number of inmates who inject drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although we found that HCV antibody prevalence was correlated overall with increasing age, a substantial number of HCV cases were identified among people who were born after 1965. 17 The objective of this study was to describe the correlates of HCV infection in the New York City jail population after the initiation of birth cohort screening. To date, the correlates of HCV infection in jail settings have been poorly characterized.…”
mentioning
confidence: 99%
“…United States jails detain those awaiting trial or serving sentences of maximum 1-year duration. Among individuals tested in the New York City (NYC) jails during 2013–2014 using a risk factor-based and 1945–1965 birth cohort-based screening strategy, 21% were HCV antibody-positive [ 2 ]. Achieving national goals for HCV elimination [ 3 ] will require scaling up treatment for people who are incarcerated, including those in jail.…”
mentioning
confidence: 99%